Perilaku Pencegahan HIV/AIDS pada Remaja: Self-Efficacy, Perceived Benefits dan Behavioral Intentions - Witdiawati Witdiawati; Nisa Humaerotul Jannah; Umar Sumarna; Dadang Purnama (Malahayati Nursing Journal, 2023)
ABSTRACT HIV/AIDS cases in Indonesia continue to increase every year. Adolescent groups have a high risk of spreading and transmitting HIV/AIDS. The purpose of this study was to identify the behavioral features of adolescents in the prevention of HIV/AIDS. This research used quantitative descriptive method with cross sectional approach on 94 respondents of adolescents in Pangandaran Village. The behavioral instrument for HIV/AIDS prevention uses the Sexual Behavioral Abstine HIV/AIDS Questionnaire (SBAHAQ). The average age of respondents was 16.37 (SD=0.77). The highest response was women (62.8%). Most respondents already have positive behavior in HIV/AIDS prevention (76.6%), based on self-efficacy sub-variables mostly positive behavior (97.9%), perceived benefit mostly positive (97.9%) and behavior intention mostly positive (93.6%). HIV/AIDS prevention behavior is mostly good. But there are still some adolescent  who behave negatively. It is important to integrate and socialize HIV/AIDS prevention in adolescent activity programs. Further research on factors influencing adolescent behavior in HIV/AIDS prevention is needed with a larger sample size.  Keywords : Adolescent, Self Efficacy, Behavior, HIV/AIDS  ABSTRAK Kasus HIV/AIDS di Indonesia terus menerus meningkat pada setiap tahunnya. Kelompok remaja memiliki resiko yang cukup tinggi dalam penyebaran serta penularannya HIV/AIDS. Tujuan penelitian ini adalah untuk mengidentifikasi gambaran perilaku remaja dalam pencegahan HIV/AIDS. Penelitan ini menggunakan metode deskriptif kuantitatif dengan pendekatan cross sectional pada 94 responden remaja di Desa Pangandaran. Instrumen perilaku pencegahan HIV/AIDS mengunakan Sexual Behavioral Abstine HIV/AIDS Questionnaire (SBAHAQ). Rata-rata usia responden adalah 16.37 (SD=0,77). Respon terbanyak adalah perempuan (62.8%). Sebagian besar responden sudah memilki perilaku positif dalam pencegahan HIV/AIDS sebesar (76.6%), berdasarkan sub variabel self efficacy sebagian besar berperilaku positif (97.9%), perceived benefit sebagian besar positif (97.9%) dan behavior intention sebagian besar positif (93.6%). Perilaku pencegahan HIV/AIDS sebagian besar sudah baik. Namun masih ada beberapa remaja yang berperilaku negatif. Penting adanya integrasi dan sosialisasi pencegahan HIV/AIDS pada program kegiatan remaja. Penelitian lanjutan terkait faktor-faktor yang mempengaruhi perilaku remaja dalam pencegahan HIV/AIDS diperlukan dengan jumlah sampel yang lebih besar.  Kata Kunci : Remaja, Self Efficacy, Perilaku, HIV/AIDS